Fabrateria Nova, Italien: San Giovanni Incarico, Provinz Frosinone - Fröhlich, Thomas (e-Forschungsberichte des DAI, 2023)
The project, starting in 2007, is a collaboration of Italian and German researchers. It focuses on the outset and development of the urban structure as well as the public and private spaces of the colony Fabrateria Nova, founded by the Romans in 124 BC in central Liri valley in south Latium. A short geophysical campaign in 2013 produced useful information on the enclosing structures of the republican terrace with three temples in the eastern part of the town. Furthermore, on the western side of an early-imperial porticus, possibly the forum of the colony, a series of regular constructions orientated towards this open yard can be assumed.